Correlation Analysis between Traditional Chinese Medicine Syndromes and Gastrointestinal Bleeding after Percutaneous Coronary Intervention. (31st May 2018) - Zhang, Chenhao; Huang, Chaolian; Wang, Mingming; Kong, Xiaolin; Liu, Guannan; Wang, Jie
Abstract : Objective. To explore the characters of traditional Chinese medicine (TCM) syndromes after percutaneous coronary intervention (PCI) and to provide syndrome study theoretical evidence for TCM differentiation treatment after PCI through retrospective study. Methods. Patients with coronary heart disease (CHD) who underwent PCI in Cardiovascular Intervention Center of Wangjing Hospital during Dec. 2012 to Dec. 2014 and met the inclusion criteria were enrolled. Retrospective study was then conducted based on patients' clinical document and angiography data to explore the distribution pattern of TCM syndromes. Results. 801 patients were recruited in the study. TCM syndromes in descending order of their incidence were Qi deficiency and blood stasis syndrome, heart blood stasis syndrome, Qi and Yin deficiency syndrome, phlegm and blood stasis syndrome, Qi stagnation and blood stasis syndrome, Yang asthenia syndrome, heart and kidney yin deficiency syndrome to cold congeal, and blood stasis syndrome in a more to less order. Qi deficiency and blood stasis syndrome was in the most (occurring in 298 patients, 37.20%); Qi and Yin deficiency syndrome occurred in 163 patients (20.35%); heart blood stasis syndrome was shown in 126 patients (15.73%); phlegm and blood stasis syndrome was shown in 95 patients (11.86%). Conclusion. Qi deficiency and blood stasis syndrome was closely associated with post-PCI bleeding, implying that this syndrome might serve as a powerful predictor of GI bleeding as well as a potential supplement to the current predicting and scoring system of bleeding such as CRUSADE.